Morphometric, meristic and growth patterns ofMotan Fish (Thynnichtys thynnoides Bleeker 1852) from the Tanjung Kudu Lake, Kualu village, Mining District Kampar Regency Riau Province - Sri Rahayu Rezki Ardiyanti; Ridwan Manda Putra; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThynnichtys thynnoides (motan fish) is one of the freshwater fish that inhabit the Tanjung Kudu Lake. This fish has high economic value and has a delicious and tasty meat. The price of motan fish in the market ranges from around Rp. 20.000-30.000/kg. To understand the morphometric, meristic and growth pattern of this fish, a research was carried out in Tanjung Kudu Lake from September-November 2020. The number of fish caught from the lake was 111 fishes (79-157 mm TL and 3-42 gr BW). There were 26 morphological characteristic measured and 9 meristical characteristic observed. General body from of the fish is not changing as the fish growing. The meristic characteristic of the fish were as follow : D.I.8-10, P.10-7, V.II.7-9, A.4-7.3, C.12-22.8, while the number of scale in the frontal area of the dorsal fin was 10-27, around the body was 20-44, around the base of the tail was 12-27 and in the lateral line was 36-65. The length-weight relationship shown that the growth of male is positive allometricin male (b = 3.6241) and in female (b = 3.6737).Keyword: Thynnichtys thynnoides, Tanjung Kudu Lake, Morphometric, Meristic, positive allometric.